Students' Mathematical Communication Ability through the Brain-Based Learning Approach using Autograph - Triana, Mailis; Zubainur, Cut Morina; Bahrun, Bahrun (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2019)
AStudents’ skills in expressing mathematical ideas in various ways have not met the expectation. Teachers need to apply the learning providing students’ opportunities to present their mathematical ideas. Utilizing the Brain-Based Learning (BBL) approach with Autograph can help students develop their mathematical communication skills. The purpose of this study was to analyze the development of students’ mathematical communication skills. Twenty-eight 10th grade students in one of the high schools in Banda Aceh participated in the study. The instruments used were a mathematical communication skills test and the activity observation. Data were analyzed using descriptive analysis. The study showed that mathematics learning applying BBL approach with Autograph contribute to developing students’ mathematical communication skills.